Studi Eksperimental Pengaruh Konfigurasi Penampang Sekat Terhadap Kinerja Novel Cooling Tower Prototype - Afandi, Dedi; Syuhada, Ahmad; Sary, Ratna; Zulfan, Zulfan; Yufandi, Asra (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2022)
Cooling towers are widely applied in industries such as power plants and oil refineries, where the equipment produces excess heat that needs to be removed. The effect of baffles configuration on the performance of the novel cooling tower prototype was studied experimentally. The configuration of the baffles used is the baffle section without holes, the baffle section with 15 holes, the baffle section with 25 holes, and the baffle section with 35 holes. The water inlet temperature was varied, namely 55⁰C, 75⁰C, and 90⁰C. water is flowed from the main reservoir to the upper reservoir of the cooling tower using a pump, and water from the upper reservoir falls on the baffles of the cooling tower. Inlet water temperature, outlet water temperature, and water temperature at each baffle were measured using a thermocouple. The results showed that the cooling tower with a baffle of 35 holes produced the most optimal performance. The heat transfer rate produced by the cooling tower with a 35-hole baffle at an inlet temperature of 55⁰C is 624.64 Watts. At the water inlet temperature of 75⁰C, the average heat transfer rate produced by the cooling tower with a 35-hole baffle increased by 42.6%. The average heat transfer rate produced by a cooling tower with a 35-hole baffle at a water inlet temperature of 90⁰C increased by 62.6%. This is because the cooling tower with a baffle of 35 holes causes the water droplets that pass through the baffle to split into more and more so that the heat transfer rate is higher.